Impelementasi Faktor Kebijakan Pemerintah Daerah dalam Penanganan Banjir (Studi Kasus: Kecamatan Ciledug Kota Tangerang) - Huda Mubarok, Ahmad Sabili; Murodi, Ahmad; Firdiyani, Fitria (Peneliti.net, 2024)
Flood is a seasonal disaster that occurs in Ciledug District, Tangerang City with an average water level of 1-3 meters. Factors such as overflowing Angke River, lack of water catchment areas, drainage that is not functioning optimally, and lack of community participation in protecting the environment affect this. The research was conducted with the aim of knowing the root causes and actions that need to be taken in implementing flood management in Ciledug District, Tangerang City. The research method was carried out in a descriptive-qualitative manner through observation, interviews, and documentation, to then be processed through data triangulation. The results showed that the implementation of the handling of the Regional Disaster Management Agency (UPT BPBD) in Ciledug District was in accordance with the concept of flood management from George Edward III's theory. Shown by a decrease in the number of flood points, a more controlled volume of water, and a shorter duration of water absorption. The community, especially the Tajur sub-district feel the positive effects of this implementation. The concept of flood management can be a guide for the government in improving flood management policies in the future to improve environmental health and community welfare.